The Role of Earning Quality, Audit Quality and Independent Commissioner in Suppressing Tax Avoidance Practice - SOLIKHAH, Badingatus; WAHYUDIN, Agus; PURWANINGSIH, Septya; SURYARINI, Trisni (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019DO - 10.14505/jarle.v10.8(46).30, 2019)
Aggressive tax planning is a threaten government revenue in many countries, so tax avoidance has become an international political issue nowadays. The objectives of this study were to observe the trends in tax avoidance practices in manufacturing companies in Indonesia and to examine the influence of earnings management, proportion of independent commissioners, and audit quality toward the possibility of companies in reducing tax costs. The practice of tax avoidance is measured by the Cash Effective Tax Rate (CETR) as it is not affected by changes in estimates such as valuation allowance or tax protection. Aggressive practices in minimizing the tax burden still occur in Indonesia, but this study showed encouraging evidence since the trend of tax avoidance practices is gradually decreasing. The result of testing factors which affect tax avoidance that the variable proportion of independent directors was proven to be able to reduce the action of reducing the tax burden, thus independent party supervision needed to be improved. The government needed to enforce regulations through increased transparency and disclosure, closing the loophole on taxation rules, and raising awareness for taxpayers through improving tax policies and increasing accountability for channeling tax funds.